Theoretical-Methodological Reflections for the Approach to Older Adults in Vulnerable Situations: From Social Education to Social Pedagogy, a Study in the Province of Alajuela, Costa Rica - Badilla Zamora, Isabel (2021)
This article systematizes theoretical and methodological considerations to care to vulnerable elders. It also systematizes the experiential process in jointly building a network of older adults in Santa Rita de Alajuela, as part of the 2013-2018 Social Pedagogy project being implemented by Universidad Nacional de Costa Rica (UNA) at Centro de Investigación y Docencia en Educación (CIDE) [Center for Education Teaching and Research] of UNA’s Division of Basic Education (DEB). The methodology is based on the naturalistic paradigm and holds that participating adults and older adults are both builders of previous stages and social actors at current stages in their lives. This field is addressed by social pedagogy through participatory action research. A conclusion reached by the research team in the project is that the elderly population in this type of community requires not only care and healthcare but also leisure and recreational spaces as tools to improve health thoroughly. This will result, in turn, in enjoyment, well-being, and quality of life and will be reflected in the emotional and physical health of the elderly.